2008
DOI: 10.1007/s00228-008-0535-1
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetics of domperidone in preterm neonates

Abstract: This pilot study designed with a limited sampling strategy showed that domperidone plasma concentrations were consistent with those reported in adults, suggesting that domperidone dosage regimen currently used in preterm neonates is suitable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…There are some methods that have been published for the determination of domperidone in biological matrices. HPLC coupled with fluorescence detection (Dailly et al ., ; Michaud et al ., ) was reported in several studies, but those methods were time‐consuming and usually had low sensitivity. LC‐MS provided another possibility to determine domperidone in various matrices (Li et al ., ; Wu et al ., ).…”
Section: Introductionmentioning
confidence: 98%
“…There are some methods that have been published for the determination of domperidone in biological matrices. HPLC coupled with fluorescence detection (Dailly et al ., ; Michaud et al ., ) was reported in several studies, but those methods were time‐consuming and usually had low sensitivity. LC‐MS provided another possibility to determine domperidone in various matrices (Li et al ., ; Wu et al ., ).…”
Section: Introductionmentioning
confidence: 98%
“…In addition, the P450 system seems to be less developed in the preterm infant, and so the risk of toxicity is high. 9, 14 Dailly et al 15 showed that there is no clinically relevant change in domperidone elimination in preterm neonates. However, therapeutic concentrations can be different between adults and preterm neonates.…”
Section: Discussionmentioning
confidence: 99%
“…The silylated samples were then analyzed by GC/MS using selected ion monitoring (SIM) with linearity over the range 0.25-10 mgAEml )1 . Similarly, Dailly et al (15) have reported the use of LLE in a HPLC determination of domperidone in plasma in a pharmacokinetic study involving preterm neonates. In this method, 400 ll of plasma was used in the extraction and analysis involved reverse-phase HPLC and florescence detection resulting in a limit of quantification (LOQ) of 2 ngAEml )1 although the linear range was not detailed.…”
Section: Determination Of Drugs In Plasma/serummentioning
confidence: 98%